2015
DOI: 10.1002/ajmg.a.37006
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia, emotion perception, and social assertiveness in adult women with Noonan and Turner syndromes

Abstract: Noonan syndrome (NS) and Turner syndrome (TS) are associated with cognitive problems and difficulties in affective information processing. While both phenotypes include short stature, facial dysmorphisms, and a webbed neck, genetic etiology and neuropsychological phenotype differ significantly. The present study examines putative differences in affective information processing and social assertiveness between adult women with NS and TS. Twenty-six women with NS, 40 women with TS, and 40 female controls were ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 59 publications
2
12
0
Order By: Relevance
“…The NS group scored poorly on the scales measuring coherence, appropriate initiation, use of context and interests. This finding is consistent with earlier studies reporting related problems, such as social interaction, social cognition and alexithymia, making it problematic to meet the needs of the conversational partner, make correct inferences and give socially appropriate responses (Roelofs et al, 2015; Verhoeven et al, 2003; Wingbermühle et al, 2012). The results of this study revealed various language profiles in children with NS, including PLI profiles, SLI profiles and generally weak linguistic profiles.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The NS group scored poorly on the scales measuring coherence, appropriate initiation, use of context and interests. This finding is consistent with earlier studies reporting related problems, such as social interaction, social cognition and alexithymia, making it problematic to meet the needs of the conversational partner, make correct inferences and give socially appropriate responses (Roelofs et al, 2015; Verhoeven et al, 2003; Wingbermühle et al, 2012). The results of this study revealed various language profiles in children with NS, including PLI profiles, SLI profiles and generally weak linguistic profiles.…”
Section: Discussionsupporting
confidence: 91%
“…According to Pierpont (2015), social aspects of language might be affected in NS, and it is not clear whether the prevalence of autistic features is a consequence of intellectual, communicatory or sensory impairments typical for NS. Other explanations of the autistic-like behaviour are deficits in social interaction (reciprocity) or social cognition, or alexithymia (problems talking about emotions) (Roelofs et al, 2015; Verhoeven et al, 2003; Wingbermühle et al, 2012). Pierpont (2015) asks for studies assessing pragmatic language and social communication in individuals with NS.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to struggling to recognize emotional faces, girls with TS also demonstrate alexithymia, the inability to name and describe emotions (Roelofs et al, 2015). Poor emotion processing negatively impacts empathic accuracy, given the considerable overlap in self and other processing in this domain (Ochsner et al, 2008;.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, memory for faces , eye gaze (Elgar et al, 2002;Lawrence et al, 2003;Mazzola et al, 2006) and affect recognition (Anaki et al, 2016;Good et al, 2003;Hong et al, 2014;Lawrence et al, 2003b;Mazzola et al, 2006;Roelofs et al, 2015;Ross et al, 2004Ross et al, , 2002 deficits were found. For affect recognition tasks requiring participants to identify the emotions associated with static pictures of faces, girls with TS demonstrate impaired recognition for negative emotions, yet intact recognition for positive emotions (Hong et al, 2014;Lawrence et al, 2003b;Mazzola et al, 2006;McCauley et al, 1987;Skuse, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…The decisive factor for the further development of the child and the planning of specialist care is the rapid identification of the disease. The fact is that the identified mutation in the RAF1 gene in patients with NS does not mean they are predestined to develop psychomotor disorders [22,23].…”
Section: Discussionmentioning
confidence: 99%